A systematic review of hospitalization resulting from medicine‐related problems in adult patients. (August 2014) - Al Hamid, Abdullah; Ghaleb, Maisoon; Aljadhey, Hisham; Aslanpour, Zoe
<x xml:space="preserve">Abstract</x> Aims Medicine‐related problems (MRPs) represent a major issue leading to hospitalization, especially in adult and elderly patients. The aims of this review are to investigate the prevalence, causes and major risk factors for MRPs leading to hospitalization in adult patients and to identify the main medicine classes involved. Methods Studies were identified through electronic searches of Medline, Embase, Scopus and International Pharmaceutical Abstracts between January 2000 and May 2013. A systematic review was conducted of both retrospective and prospective studies. Studies included were those involving hospitalization resulting from MRPs in adults (≥18 years old), whereas studies excluded were those investigating drug misuse and abuse and studies investigating MRPs in hospitalized patients. Data analysis was performed using SPSS version 20. Results Forty‐five studies were identified, including 21 that investigated hospitalization resulting from adverse drug reactions, six studies that investigated hospitalization due to adverse drug events and 18 studies that investigated hospitalization due to MRPs. The median prevalence rates of hospitalization resulting from adverse drug reactions, adverse drug events and MRPs were 7% (interquartile range, 2.4–14.9%), 4.6% (interquartile range, 2.85–16.6%) and 12.1% (interquartile range, 6.43–22.2%), respectively. The major causes contributing to MRPs were adverse drug reactions and noncompliance. In addition, the major risk factors associated with MRPs were old age, polypharmacy and comorbidities. Moreover, the main classes of medicines implicated were medicines used to treat cardiovascular diseases and diabetes. Conclusions Hospitalization due to MRPs had a high prevalence, in the range of 4.6–12.1%. Most MRPs encountered were prevalent among adult patients taking medicines for cardiovascular diseases and diabetes.